Better before–better after: efficacy of prehabilitation for older patients with osteoarthritis awaiting total hip replacement—a study protocol for a randomised controlled trial in South-Eastern Norway - May Arna Risberg; Are Hugo Pripp; Astrid Bergland; Odd-Einar Svinøy; Gunvor Hilde (BMJ Open)
Introduction Health professions need to prepare for the increase of older patients with osteoarthritis requiring health services including those requiring total joint arthroplasty (TJA). The primary objective of this study is to assess the effect of a tailored prehabilitation programme of older patients awaiting primary surgery for total hip replacement on physical function measured by walking speed within 1 week after intervention as well as 6 weeks and 3 months after TJA surgery.Methods and analysis This is a single-blinded randomised controlled trial. The participants are 70 years or older, scheduled for primary total hip replacement due to late stage osteoarthritis. The intervention group will receive patient education and exercise for 6–12 weeks. The control group will receive care as usual. The primary outcome is gait speed. Secondary outcomes are lower body strength, mobility, aerobic capacity, activity of daily living, length of stay at the hospital, referral to an inpatient rehabilitation clinic, pain, quality of life and cost-effectiveness. Estimated sample size is 150 participants randomised into the two arms. The data will be analysed following the intention-to-treat principle with methods for repeated measurements.Ethics and dissemination The project proposal has been approved by The Regional Committee for Medical Research Ethics in South Norway (ref no. 2018/503). The results will be published in peer-reviewed articles.Trial registration number NCT03602105